Godzilla: here there be dragons (2023) ebook - Tieri, Frank (Godzilla: Here There Be Dragons (2023), 2024)
In the 1500s, a ship of seafaring navigators run afoul of a lost world where there is only one king, the King of the Monsters! Before humanity had successfully traveled the entire globe, it was believed that monsters ruled the oceans just beyond the horizon. “Here there be dragons…” was written on maps to denote the areas people dared not go.That is, until Sir Francis Drake circumnavigated the seas, visiting foreign lands and collecting treasure. That’s what history tells us, at least, but history does not have the full tale. Monsters did lurk yonder, living on an island that still doesn’t appear on any map, and among them was the king of them all…Godzilla! From Frank Tieri and Inaki Miranda, the incredible team behind Old Lady Harley, comes a Godzilla adventure like no other. Collects the five-issue series.